2014
DOI: 10.1021/jp509191b
|View full text |Cite
|
Sign up to set email alerts
|

Role of Complex Surface Tension in the Dispersion Relation of a Capillary Wave

Abstract: We discuss theoretically the effect of complex surface tension on the dispersion relation of a capillary wave, and we deduce an analytical expression for the attenuation of a capillary wave due to the imaginary part of the complex surface tension. We make use of our recently developed apparent energy dissipation spectroscopy to measure the attenuation of a propagating capillary wave at an air− water interface via a microrheometer based on an atomic force microscope. We show that the revised theoretical express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Finally, recent measurements of the dissipation associated with periodic modulation of air–water surface area disclosed enhanced frequency dependent dissipation, which was too large to be accounted for by bulk water properties . The authors of ref suggested that the excess dissipation stems from a complex surface tension coefficient which may explain the large dissipation seen here following the cavitation transition and the formation of a new water–vapor interface. Within the cavitation scenario, the tip oscillation should lead to an oscillatory variation in the capillary surface area and hence, assuming a complex surface tension coefficient, to dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent measurements of the dissipation associated with periodic modulation of air–water surface area disclosed enhanced frequency dependent dissipation, which was too large to be accounted for by bulk water properties . The authors of ref suggested that the excess dissipation stems from a complex surface tension coefficient which may explain the large dissipation seen here following the cavitation transition and the formation of a new water–vapor interface. Within the cavitation scenario, the tip oscillation should lead to an oscillatory variation in the capillary surface area and hence, assuming a complex surface tension coefficient, to dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…This term is not defined. The contact angle on the fiber is shown as an unlikely 90° at a flat surface in ref and as swinging between ∼45 and ∼135° at the terminus of the standing wave at the fiber in ref . Such a “swing” would constitute a cycle of large positive and negative contributions to the vertical force on the fiber registered by the cantilever, which is not observed, but the geometries and associated displacements at the fiber surface may not be ignored.…”
Section: Analysis Of the New Experimentsmentioning
confidence: 91%
“…An instructive experiment would be to compare the force profile and power dissipation when withdrawing the fiber through the water surface, for comparison with the reported experiments, which appear to always be in the advancing mode. Varying the tapping amplitude would be similarly instructive Chen et al 4 cite the early light-scattering results of Hammarlund et al 19 on aqueous solutions of carboxymethylcellulose in support of their conclusions from the AFM-fiber measurements on water. From a reanalysis of the light scattering data (presumably for the source water) as interpreted with their model, they conclude that wave damping from the imaginary part of the surface tension is larger than the contribution from the bulk solution viscosity, leading to an estimate of the imaginary part of the surface tension in agreement with that estimated from their AFM-fiber experiments.…”
Section: ■ Introductionmentioning
confidence: 88%
See 2 more Smart Citations